2013
DOI: 10.14419/ijans.v2i2.578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-nutritive sucking and leg massage on physiological and behavioral indicators of pain following heel blood sampling in term neonates

Abstract: Background: Pain management is especially important for neonates who are not able to verbally express their pain. Non-pharmacological pain management method as an alternative to pharmacological pain medication has increased nowadays. Objectives: The purpose of this study was to test the effect of leg massage and non-nutritive sucking (NNS) on reducing the pain that neonates experience when undergoing the heel stick procedure for blood testing. Methods: This investigation was a random controlled clinical trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 18 publications
2
24
0
8
Order By: Relevance
“…These findings were consistent with previous studies in the area exploring multiple pain stimuli and pain assessment tools. For instance, Mirzarahimi M et al (2013) reported the efficacy of NNS in alleviating pain during heel blood sampling in term neonates using the PIPP pain score, when compared to the control group. 15 Another RCT by Liaw JJ et al (2011) also showed that the NFCS pain scores in infants receiving NNS were lower compared to the control group during intramuscular injections for hepatitis vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent with previous studies in the area exploring multiple pain stimuli and pain assessment tools. For instance, Mirzarahimi M et al (2013) reported the efficacy of NNS in alleviating pain during heel blood sampling in term neonates using the PIPP pain score, when compared to the control group. 15 Another RCT by Liaw JJ et al (2011) also showed that the NFCS pain scores in infants receiving NNS were lower compared to the control group during intramuscular injections for hepatitis vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Mirzarahimi M et al (2013) reported the efficacy of NNS in alleviating pain during heel blood sampling in term neonates using the PIPP pain score, when compared to the control group. 15 Another RCT by Liaw JJ et al (2011) also showed that the NFCS pain scores in infants receiving NNS were lower compared to the control group during intramuscular injections for hepatitis vaccination. 18 16 Similarly, the NIPS pain scores in infants receiving NNS during venipunctures was lower than those in the control group in a 2010 study by Liu M et al 19 In contrast, Kristoffersen et al revealed that infants in the control group had lower PIPP pain scores than those receiving NNS during a feeding tube insertion procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Teori tersebut menyatakan bahwa pada masa neonatus, BBLR berada pada tahap perkembangan oral, sehingga penghisapan akan memberikan rasa nyaman. Keterbatasan intervensi pemberian empeng adalah kurang menerapkan prinsip family centered care (Mirzarahimi, Mehrnoush, Shahizadeh, Samadi, & Amani, 2013).…”
Section: Gambar 1 Rata-rata Skor Nyeri Berdasarkanunclassified
“…Pelaksanaan intervensi pemberian empeng dipengaruhi oleh rasa lapar, ketidaknyamanan, temperamen BBLR, status bangun dan tidur, serta pengalaman nyeri (Mirzarahimi et al, 2013).…”
Section: Gambar 1 Rata-rata Skor Nyeri Berdasarkanunclassified
“…In 1998, the American Academy of Pediatrics declared full oral feeding tolerance as a discharge criterion (14). Today, several studies are conducted on NNS in preterm neonates to maximally speed up independent oral feeding (15)(16)(17)(18). Non-nutritive feeding during gavage increases the secretion of digestive enzymes and improves digestion (12,19,20).…”
Section: Introductionmentioning
confidence: 99%